Prospects for variety selection of spring wheat Open Company «the Kazakh scientific research institute of agriculture and plant growing» JSC «КаzАgroInnovation» MSH RK (Experimental biology, 2015)
The paper presents the results of selective breeding to produce new varieties of spring wheat of Open Company «Тhe Kazakh scientific research institute of agriculture and plant growing», and shows the areasoccupied in the production of these varieties in the Republic of Kazakhstan, which in 2011 amounted to 791 750 hectares. On results state varieties research they were very competitive in comparison with other varieties breeding scientific research institute of Kazakhstan and Russia in the Northern, Eastern and Southern Kazakhstan, which determines their prospects implementation in production.
Keywords: breeding; culture; spring soft wheat; sort; productivity; areas occupied